2018
DOI: 10.1016/j.ekir.2018.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Successful Use of Renal Denervation in Patients With Loin Pain Hematuria Syndrome—The Regina Loin Pain Hematuria Syndrome Study

Abstract: IntroductionLoin pain hematuria syndrome (LPHS) is characterized by severe unilateral or bilateral loin pain that suggests a renal origin but occurs in the absence of identifiable or relevant urinary tract disease. Hematuria can either be microscopic or macroscopic, but the renal abnormalities responsible for the hematuria are unexplained. Debilitating pain refractory to conventional pain medications is the main cause of morbidity.MethodsWe conducted a single-arm, single-center study. Twelve patients between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Case reports and series from our group and others have shown renal denervation via catheter-based radiofrequency ablation to be an effective therapeutic option for the treatment of LPHS. [10][11][12][13][14] Randomized clinical trial studies are now needed to establish the efficacy of catheter-based renal denervation as a mainstream treatment option in LPHS patients.…”
Section: Problem To Be Addressedmentioning
confidence: 99%
See 3 more Smart Citations
“…Case reports and series from our group and others have shown renal denervation via catheter-based radiofrequency ablation to be an effective therapeutic option for the treatment of LPHS. [10][11][12][13][14] Randomized clinical trial studies are now needed to establish the efficacy of catheter-based renal denervation as a mainstream treatment option in LPHS patients.…”
Section: Problem To Be Addressedmentioning
confidence: 99%
“…The reduction in pain was accompanied by considerable improvement in functionality, mood, and quality of life. 14 De Jager et al also reported on successful outcomes in 11 patients (6 patients with LPHS and 5 patients with autosomal dominant polycystic kidney disease). A sustained pain reduction effect (up to 12 months) and a significant reduction in medication use were reported in this study.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Up to now, the pathogenesis is unclear. Pain attacks have been described as severe to extremely severe and have led to a spectrum of non-surgical therapeutic strategies [ 4 ]: analgesics including opioids, ACE-inhibitors [ 8 ], nerve blockade [ 9 , 10 ], dorsal root ganglion stimulation [ 11 , 12 ], intraureteric capsaicin [ 13 ], etc. Surgical strategies range from renal autotransplantation [ 14 , 15 ] to bilateral nephrectomy [ 16 ].…”
Section: Introductionmentioning
confidence: 99%